1) Take everything without an x or y to the right.
x² - 2x + y² - 4y = 4
2) For each of the terms that has only x or only y:
2a) Divide the coefficient by 2. -2/2 = -1, -4/2 = -2.
2b) Square that number: (-1)² = 1, (-2)² = 4.
2c) Add those numbers to both sides.
x² - 2x + 1 + y² - 4y + 4 = 4 + 1 + 4
3) You now have two perfect squares for x and y on the left, and the radius squared on the right.
(x - 1)² + (y - 2)² = 9 = 3²
Since this is in the correct form:
(x - h)² + (y - k)² = r²
the answer is: center (1, 2), radius 3.
2007-01-12 13:52:43
·
answer #1
·
answered by Jim Burnell 6
·
1⤊
0⤋
x^2-2x+y^2-4y-4=0
Now, the equation is (x-h)^2+(y-k)^2=r^2. Let's try to get to this form. First we add four to both sides to remove that -4. That gives
x^2-2x+y^2-4y=4. Next we "complete the square"
x^2-2x(+1)+y^2-4y(+4)=4(+1)(+4)
Adding 1 made x^2-2x+1, which is (x-1)^2. Adding another 4 made y^2-4y+4, which is (y-2)^2. This is why we call it "completing the square", we add numbers to make perfect squares of algebraic expressions. Now we have
(x-1)^2+(y-2)^2=9
This is in the form of (x-h)^2+(y-k)^2=r^2. Since 3^2=9, h=1, k=2, and r=3.
Therefore, the center is (1,2), and the radius is 3.
2007-01-12 14:20:07
·
answer #2
·
answered by dennismeng90 6
·
0⤊
0⤋
x^2 - 2x + y^2 - 4y - 4 = 0
x^2 - 2x + y^2 - 4y = 4
(x^2 - 2x) + (y^2 - 4y) = 4
(x^2 - 2x + 1 - 1) + (y^2 - 4y + 4 - 4) = 4
((x - 1)^2 - 1) + ((y - 2)^2 - 4) = 4
(x - 1)^2 - 1 + (y - 2)^2 - 4 = 4
(x - 1)^2 + (y - 2)^2 - 5 = 4
(x - 1)^2 + (y - 2)^2 = 9
The standard form of a circle is
(x - h)^2 + (y - k)^2 = r^2
whereas (h,k) is the center and "r" is the radius
ANS :
Center = (1,2)
Radius = 3
2007-01-12 15:16:08
·
answer #3
·
answered by Sherman81 6
·
0⤊
0⤋
You have to complete 2 squares
x^2-2x+y^2-4y-4=0
(x^2-2x+1) +(y^2-4y+4) -4-1-4=0
(x-1)^2+(y-2)^2=9=3^2
The center is at (1, 2) & the radius is 3
2007-01-12 14:36:42
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
x^2-2x + y^2 -4y -4= 0
(x^2-2x +1) + (y^2 - 4y + 4) = 9
(x-1)^2 + (y-2)^2 = 3^2
This is the equation of a circle with center C(1,2) and radius 3.
2007-01-12 14:15:43
·
answer #5
·
answered by JasonM 7
·
0⤊
0⤋
x^2-2x + y^2 -4y -4= 0
(x^2-2x +1) + (y^2 - 4y + 4) = 9
(x-1)^2 + (y-2)^2 = 3^2
the center is at (1,2) and the radius is 3.
2007-01-12 13:59:49
·
answer #6
·
answered by Brian F 4
·
0⤊
0⤋
a million. aspect thoroughly: x^2 + 10x + 25 A) (x + 5)(x - 5) B) (x + 5)(x + 5) C) (x - 5)(x - 5) D) (x + 25)(x + a million) answer is B. x*x =x^2; 5*5=25; 5*x+5*x =10x 2. aspect thoroughly: 3x^2 - 12 A) 3(x^2 - 4) B) 3(x + 2)(x + 2) C) 3(x + 2)(x - 2) D) (x + 2)(x - 2) answer is C. A is genuine yet did not go far sufficient. x^2-4 will be factored to (x+4)(x-4). 3. aspect thoroughly: 2x^2 - x - 10 A)(2x - 5)(x + 2) B) (2x + 5)(x - 2) C) (2x + 5)(x + 2) D) (2x - 5)(x - 2) answer is A. 2x*x =2x^2; (-5)(2)=-10;(-5)x +(2x)2 = -x 4. Simplify thoroughly: (4x -8) / (x-2) A) 4(x-2) / (x-2) B) 4 C) 8 D) 3x+4 answer is B. A did not cancel the x-2 words to get 4. it might that x won't be able to be equivalent to 2 or you need to be dividing by technique of 0 that is a no-no
2016-11-23 15:08:33
·
answer #7
·
answered by ? 4
·
0⤊
0⤋
you have to get in the form
(x-a)^2 +(y-b)^2 = c^2
now (x^2-2x) = x^2+2(x)(-1)+(-1)^2 -1 = (x-1)^2 -1
as (x-a)^2 = x^2 -2 a x + a^2
2ax = 2x so a =1 so add 1-1 when you add 1 it will complete the square and then subtract 1 for compasation
similarly
(y^2-4y) = (y-2)^2 - 4
we get (x-1)^2-1 + (y-2)^2 -4 -4 = 0
or (x-1)^2+(y-2)^2 = 9 = 3^2
so centre is (1,2) radius is 3
2007-01-12 13:57:24
·
answer #8
·
answered by Mein Hoon Na 7
·
1⤊
0⤋